Investigation of novel immobilized 3-(perfluoroalkanoyl)-(1R)-camphorate nickel complexes in enantioselective complexation gas chromatography - Stockinger, Skrollan Carina; Spallek, Markus Jürgen; Trapp, Oliver (Journal of chromatography, 2012)
Novel 3-(perfluoroalkanoyl)-(1R)-camphorate nickel complexes immobilized to poly(dimethylsiloxane) phases are presented. Immobilized 3-(perfluoroalkanoyl)-(1R)-camphorate nickel complexes with a trifluoromethyl (CF3; nickel(II)-bis[(1R,4S)-3-trifluoromethanoyl-10-propylenoxycamphor]-polysiloxane Ni(tfpc)2PS) and a heptafluoropropyl-substituent (C3F7; nickel(II)-bis[(1R,4S)-3-heptafluorobutanoyl-10-propylenoxycamphor]-polysiloxane Ni(hfpc)2@PS) were synthesized, characterized and immobilized to polysiloxane. Ni(hfpc)2@PS was immobilized with a selector content of 38% and their enantioseparation ability was compared to selector concentrations of 4% and 20%. The influence of the perfluorinated moiety as well as the effect of the selector concentration on enantioseparations were investigated. Based on different functionalized organic compounds the quality of enantioseparation was analyzed and compared.
Gesehen am 28.08.2020